A Content Analysis of Undu-unduon as a Cultural Reflection of Saluan Ethnic Group - Peni Lombua; Sri Julikasari Monggiapon; Maria Lumantow; Nadya Septiani Rahman; Anitha Thalib Mbau (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
This study explores Undu-unduon, the oral folktales of the Saluan people in Central Sulawesi, as a medium of cultural preservation and identity formation. Despite the pressures of globalization and technological change, these narratives remain vital in transmitting values across generations. The research aims to identify the moral, social, and cultural wisdom contained in the stories and to explain their role in reflecting Saluan identity. Using Krippendorff’s content analysis, nine folktales were examined through interviews with cultural bearers, published collections, and digital recordings. Each narrative was coded into categories of moral values, social relations, cultural beliefs, and identity markers. The findings reveal that the tales embed lessons of honesty, responsibility, discipline, and respect for elders, while also warning against greed, betrayal, and disobedience. Stories such as Burung Popongku, Danau Dowiwi, and Banangsina highlight discipline, kinship, and resilience as core elements of Saluan worldview. At the same time, they critique negative behaviors that disrupt social harmony. The study concludes that Undu-unduon functions not only as entertainment but also as moral instruction and cultural preservation, offering insights into how oral traditions can be used to strengthen character education and sustain ethnic identity in modern contexts.